The Teaching Profession from the Perspective of Novice Primary School Teachers - Responsibility and Joy - Jana Stará; Radka Wildová; Šárka Popelková (Charles University, 2020)
There is a great deal of interest in researching the perception of teachers about their first years in teaching; however, the research does not often focus on examining the views of primary school teachers. This is despite the fact that their multidisciplinary training, their multidimensional role, and their teaching practice, usually tied to one class group, may lead to their different perception of the first years in practice and therefore to other needs in the field of their support. This article will present the results of a questionnaire survey focused on the perception of the teaching profession during the first years of practice among graduates of the Primary School Teacher Training study programme at the Faculty of Education of Charles University. The respondents show a positive attitude towards the profession; they say that teaching brings them joy and fulfilment. At the same time, they are aware of the great responsibility that the profession brings. From their answers it is clear they have a strong emotional connection to the children and they are interested in their cognitive development. The results of the survey also show that the respondents are sensitive to society's underestimation of the importance and complexity of the teaching profession. Keywords: newly qualified teacher, novice teacher, beginning teacher, teacher induction, primary school teaching, perception of the teaching profession